UNJUK KERJA PROSES MULTIVARIABEL REAKTOR KONTINYU DENGAN PENGENDALI LOGIKA FUZZY - Agus Suprajitno (PSTE UNIMUS, 2010)
Chemical reactors can be made continuous process mathematical model based on the law of equilibrium concentrations, the equilibrium of mass and energy balance. In this reactor modeling process is assumed to be continuous, homogeneous and endothermic, with two reactants and the reaction products. Modeling results show the influence of reactant concentration and jacket temperature on the concentration and temperature of the reaction followed a second order equation which interact to form a multivariable system. Effect of interaction can be reduced or eliminated with decoupling process. The system is controlled by fuzzy logic controllers with rule mamdani. The process is a multivariable system that has the interaction between two inputs qnd two outputs. Interaction concentrations of the reactants to the product temperature at 26% of input, interaction jacket temperature of the product concentration of 2 % of the entries shown in the graph simulation results without decoupler open. circle response. Keywords : CSTR, RGM, decoupling